Pengaruh Luas Panen Padi, Produktivitas Lahan, Pertumbuhan Harga Beras dan Jumlah Penduduk terhadap Ketersediaan Beras di Indonesia tahun 1990-2022 - Novita Nur Khasanah; Edy Yusuf Agung Gunanto (Diponegoro Journal of Economics, 2024)
Rice is main food commodity consumed in Indonesia. The availability of rice plays a strategic role in food security, national economic, and political stability. The increasing population results in an increasing demand for food, especially rice. Meanwhile, rice production fluctuates following cropping patterns and weather changes, resulting in a gap between rice availability and rice consumption. The purpose of this study is to determine the effect of rice harvest area, land productivity, rice price growth and total population on Indonesia's rice availability in 1990 to 2022 partially and simultaneously. The data used in this study is secondary data based on a time series in Indonesia from 1990 to 2022. This study was analyzed using multiple linear regression analysis with Eviews 10 application. The results of the study showed that simultaneously, rice harvest area, land productivity, rice price growth, and total population had a significant effect on rice availability. Partially, land productivity and rice price growth have a positive and significant effect on rice availability. Total population has a negative and significant effect on rice availability. Meanwhile, rice harvest area has no significant effect on rice availability.